Konektivitas Ruang Taman Vatulemo dan Kantor Walikota Palu - J, Husnirrahman; Suhardi, Cahyani; Burhanuddin, Burhanuddin (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2025)
Vatulemo Park and the Palu City Hall are two important elements in the structure of Palu city, serving as recreational public space and the center of government administration, respectively. This article aims to analyze the spatial conectivity between these two locations, focusing on physical, activity, and visual aspects. The study employs both qualitative and quantitative approaches to identify the physical relationships, activity patterns, and visual connections between Vatulemo Park and the Palu City Hall. The findings highlight the importance of physical connectivity through pedestrian pathways and accessibility facilities, as well as the need for better management in integrating public spaces and government areas.